Magnesium: Why is it so important in clinical medicine? - Wannasilp, Nilrat (Siriraj Medical Journal, 2003)
Magnesium (Mg) is the second most plentiful intracellular cation. It has many important physiologic functions, including enzyme, membrane, calcium antagonist ans structural functions. The serum contains Mg concentration less than 1% of the total body Mg, and the remainder is mostly present in the soft tissue and bone. Consequently, assessing Mg status is quite difficult. At present, the majority of clinical laboratory information fromt he determination of the total Mg concentration in serum and 24-hour urinary excretion, but instrumentations to evaluate ionized Mg and intracellular Mg should be available in the near future. Disorders of Mg metabolism, especially hypomagnesemia (Mg deficiency), are frequently observed in clinical medicine. These may play important roles in the pathophysiology of many diseases or condition, such as hypocalcemia, acute myocardial infarction and migraine. Also, Mg supplement may be a factor in the treatment of these condition, but its routine use in emergency medicine is still controversial.